2018
DOI: 10.1016/j.oregeorev.2017.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate sulfidation type base metal mineralization at Aliabad-Khanchy, Tarom-Hashtjin metallogenic belt, NW Iran

Abstract: The Aliabad-Khanchy epithermal base metal deposit is located in the Tarom-Hashtjin metallogenic belt (THMB) of northwest Iran. The mineralization occurs as Cu-bearing brecciated quartz veins hosted by Eocene volcanic and volcaniclastic rocks of the Karaj Formation. Ore formation can be divided into five stages, with most ore minerals, such as pyrite and chalcopyrite being formed in the early stages. The main wall-rock alteration is silicification, and chlorite, argillic and propylitic alteration. Microthermome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 94 publications
1
15
0
Order By: Relevance
“…The geological investigations revealed that almost all the epithermal deposits in the THMB clustered around the late Eocene (~40-36 Ma, Nabatian et al, 2014;Nabatian et al, 2016;Aghazadeh et al, 2015;Kouhestani, 2018;Mokhtari et al, 2022a) granitoid intrusions (Figure 1). There is now a broad consensus that these deposits resulted from shallow magmatichydrothermal processes related to the late Eocene magmatism (e.g., Ghasemi Siani et al, 2015;Mehrabi et al, 2016;Kouhestani et al, 2018a;b, 2020. Mehrabi et al (2016) reported a biotite Ar-Ar age of 41.87 ± 0.16 Ma for the crystallization of the Goljin granite intrusion, which was considered closely related to the Au mineralization of the Gulojeh deposit.…”
Section: Timing Of Epithermal Base Metal Mineralizationmentioning
confidence: 99%
See 3 more Smart Citations
“…The geological investigations revealed that almost all the epithermal deposits in the THMB clustered around the late Eocene (~40-36 Ma, Nabatian et al, 2014;Nabatian et al, 2016;Aghazadeh et al, 2015;Kouhestani, 2018;Mokhtari et al, 2022a) granitoid intrusions (Figure 1). There is now a broad consensus that these deposits resulted from shallow magmatichydrothermal processes related to the late Eocene magmatism (e.g., Ghasemi Siani et al, 2015;Mehrabi et al, 2016;Kouhestani et al, 2018a;b, 2020. Mehrabi et al (2016) reported a biotite Ar-Ar age of 41.87 ± 0.16 Ma for the crystallization of the Goljin granite intrusion, which was considered closely related to the Au mineralization of the Gulojeh deposit.…”
Section: Timing Of Epithermal Base Metal Mineralizationmentioning
confidence: 99%
“…A similar scenario has been documented for several epithermal deposits within the THMB, including Aliabad-Khanchy, Zajkan, Marshoun, Abbasabad, Rashtabad, Jalilabad, Aqkand, and Lubin-Zardeh. These deposits have δ 18 O water values ranging from +9.6‰ to -3.4‰ (Kouhestani et al, 2018a;b, 2020Zamanian et al, 2019), suggesting that their oreforming fluids were most likely magmatic-derived in the early stages, but were mixed with meteoric water in the late stages. It is consistent with the geological characteristics of these deposits that are indicative of an IS epithermal origin for these deposits.…”
Section: Source Of Ore-forming Fluidsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Tarom intrusions range in composition from quartz monzo-gabbro to diorite, quartz monzodiorite, monzonite, quartz monzonite, monzogranite, granodiorite, alkali granite, granite and syeno-granite (e.g., Nabatian et al 2014Nabatian et al , 2016Esmaeli et al 2015;Mehrabi et al 2016;Kouhestani et al 2017Kouhestani et al , 2018Yasami et al 2018). These I-type intrusions have high-K calc-alkaline to shoshonitic affinity and metaluminous characteristics (Irannezhadi et al 2007;Azizi et al 2009;Nabatian et al 2014Nabatian et al , 2016Yasami et al 2018) and show enrichment in Large Ion Lithophile Elements (LILE) and Light Rare Earth Elements (LREE) and negative anomalies in High Field Strength Elements (HFSE) and depletion in Heavy Rare Earth Elements (HREE) (Nabatian et al 2014(Nabatian et al , 2016Yasami et al 2018).…”
Section: Introductionmentioning
confidence: 99%